North by northwest [videorecording (DVD)] - Hitchcock, Alfred, 1899-1980; Grant, Cary, 1904-1986; Saint, Eva Marie, 1924-; Mason, James, 1909-1984 (Alfred Hitchcock collection., 2010)
A New York advertising executive is kidnapped by a gang of spies, who believe he is CIA agent accused of murder.